Tuning the Near-Infrared Absorption of Aromatic Amines on Tapered Fibers Sculptured with Gold Nanoparticles - Karabchevsky, Alina; Katiyi, Aviad; Abdul Khudus, Muhammad Imran Mustafa; Kavokin, Alexey V. (American Chemical Society, 2018)
We discover an unexpected enhancement of the absorption of near-infrared light by aromatic amine overtones on photonic microfibers sculptured with gold nanoparticles. The adsorbed nanoparticles make the near-infrared spectroscopy of aromatic amines on microfibers feasible despite the small absorption cross-section of the molecular vibration overtones. We demonstrate that in the presence of gold nanomediators, the absorption of light by weak overtone transitions in N-methylaniline as a model analyte is dramatically enhanced. We attribute this effect to the increase of the mean trajectory of light in a microfiber due to its resonant scattering on metallic nanoparticles. The spectrally integrated transmittance scales with the concentration of nanoparticles to the power 1/6 - the phenomenon of diffusive propagation of light. Practical applications of the discovered effect will include the detection of aromatic amines for efficient treatment of metabolic disorders resulting from the amino acids deficiency, research in biomedicine, and a number of bedside applications.